PERFORMANCE OF CORN SOWING IN FERTILIZATION SYSTEM AND INTERCROPPING - Cortez,Jorge W. (2018)
ABSTRACT The performance of the tractor-seeder can be influenced by factors related to the seeder, as loads and crop. The aim of the present study was to evaluate the performance of tractor-seeder at sowing in the corn crop in function of the fertilizer systems (at presowing and at sowing) and those intercropping of crops (corn + bean-Stizolobium deeringianum, corn + bean-Cajanus cajan and corn + bean-Dolichos lab lab). The experiment was carried out at FCAV-UNESP with totally randomized delineation, on factorial scheme (2x3) with four repetitions. The use of fertilization during the pre-sowing resulted in greater displacement speed and effective field capacity in the corn sowing operation, without changing the distribution of corn seeds; however, it demanded more power and volumetric and weight hourly consumption of the tractor fuel.